Prediction of RFID performance in supply chains (2010)
This paper discusses the challenges to wide-spread radio frequency identification (RFID) adoption in supply chains using the technology s-curve and the concept of buying hierarchy. A survey on RFID uptake in New Zealand is used in the discussion. We found that early adopters are faced with challenges that can be overcome by considering them early in the development stage of RFID. We look at how this set of challenges can be aligned to the development stage and proposed four issues that require early attention in order for a mass adoption to take place.